Intravenous artesunate reduces parasite clearance time, duration of intensive care, and hospital treatment in patients with severe malaria in europe: the TropNet severe malaria study - Kurth, Florian Michael; Develoux, Michel; Mechain, Matthieu; Clerinx, Jan; Antinori, Spinello; Gjørup, Ida E.; Gascon, Joaquím; Mørch, Kristine; Nicastri, Emanuele; Ramharter, Michael; Bartoloni, Alessandro; Visser, Leo; et al. (Clinical infectious diseases, 2015)
Intravenous artesunate improves survival in severe malaria, but clinical trial data from nonendemic countries are scarce. The TropNet severe malaria database was analyzed to compare outcomes of artesunate vs quinine treatment. Artesunate reduced parasite clearance time and duration of intensive care unit and hospital treatment in European patients with imported severe malaria.
Gesehen am 03.06.2020